2014
DOI: 10.4314/ahs.v14i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hen’s egg and chicken meat specific IgE antibodies in Saudi patients with allergic disorders

Abstract: Background: Allergy to hen's egg and meat contributes significantly to the manifestations of food allergy all over the world. Objectives: This study was performed to assess the presence of hen's egg and meat specific IgE antibodies among patients investigated for various allergic disorders. Methods. This is a retrospective study performed at King Khalid University Hosptial, Riyadh. Data from 421 patients with allergic disorders screened for food specific IgE antibodies between January 2009 and March 2011 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…After all, eggs are often present as an ingredient mixed with several other ingredients in one food. In Saudi food allergy, the sensitivity of egg white is higher than egg yolk [20]. Chicken is the most popular meat eaten in this country.…”
Section: Resultsmentioning
confidence: 98%
“…After all, eggs are often present as an ingredient mixed with several other ingredients in one food. In Saudi food allergy, the sensitivity of egg white is higher than egg yolk [20]. Chicken is the most popular meat eaten in this country.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, a retrospective study conducted on 421 patients in Saudi Arabia revealed that while a significant proportion of patients had s‐IgE antibodies against chicken meat, only a small proportion reacted when orally challenged with the food allergen. In addition, chicken meat antibodies coexisted in the majority of study cases with hen's egg s‐IgE and rarely appeared on their own 24 . Another potential reason why FS data do not always follow FA is that some adults will have realized what foods can cause the clinical symptoms, and will, therefore, simply stop consuming those food types for prolonged periods, yielding negative s‐IgE results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chicken meat antibodies coexisted in the majority of study cases with hen's egg s-IgE and rarely appeared on their own. 24 Another potential reason why FS data do not always follow FA is that some adults will have realized what foods can cause the clinical symptoms, and will, therefore, simply stop consuming those food types for prolonged periods, yielding negative s-IgE results.…”
Section: Discussionmentioning
confidence: 99%